VARIASI KOMPOSISI DINDING CANGKANG FORAMINIFERA BENTONIK KECIL RESEN PERAIRAN SEMARANG (LEMBAR 1409), JAWA TENGAH - -, Lia Jurnaliah (Bulletin of Scientific Contribution, 2013)
Foraminifera is a unicellular animal which has capability to form a test. Twenty samples of seafloor sediment Semarang waters are analyzed by using quantitative method. Every type of small benthic foraminifera test wall is counted. Based on foraminifera test wall analysis, there are 3 types of test wall: hyaline calcareous, porcelain calcareous, and agglutinin. The highest percentage of hyaline test is found in 24 meter, porcelain test is found in 37 meter, and agglutinin test is found in 51 meter. Hyaline test wall has the highest total individual, 140226 individual (59,45%). It shows that research area is shelf environment.